Cardiology Update - Zhu, MD, Tong (North American Journal of Medicine and Science, 2009)
Atherosclerosis causes coronary artery disease, myocardial infarction, stroke, and peripheral vascular disease.1 Our understanding of pathogenesis of atherosclerosis continues to evolve: multiple factors are involved, including endothelial dysfunction,2 dyslipidemia,3 inflammation4 and plaque rupture (Figure 1).5 This underlies the importance of pleiotropic effects of statins in treating atherosclerosis.